Tribotechnical coatings - Zemlyanoy, A.O.; Bys, S.S.; Shchepetov, V.V.; Kharchenko, S.D.; Kharhenko, O.V. (Problems of Tribology, 2024)
Wear and tear limits the possibilities and shortens the operational life of modern technical systems. Therefore, the importance and necessity of consideration of issues aimed at reducing frictional forces and increasing wear resistance cannot be doubted. The paper summarizes the theoretical and applied results of triboresistance studies of detonation coatings of the Nb-Zr-V-Si-C-MgC2 system under conditions of constant loading in the field of sliding velocities. It has been established that the ratio of the quality of the components that make up the surface modified structures changes. It is noted that at the initial test speeds the presence of lower metal carbides that are part of the coating dominates, with an increase in speed under the current load due to solid-phase and diffusion processes, higher ones are formed in the graphite matrix carbides with enhanced thermodynamic properties.